ρC(I)-COMPACT AND ρI-QHC SPACES (2016)
In this paper we introduce and investigate two new ideal topological spaces, which are strong forms of Gupta-Noiri concepts. Interesting characterizations of this spaces are presented, as well as several useful properties of these. We compare this new spaces with C-compact and quasi-H-closed spaces